Fabrication of biomaterials via controlled protein bubble generation and manipulation. - Ekemen, Z; Chang, H; Ahmad, Z; Bayram, C; Rong, Z; Denkbas, E; Stride, E; Vadgama, P; Edirisinghe, M (2011)
In this work, we utilize a recently developed microbubbling process to generate controlled protein (bovine serum albumin, BSA) coated bubbles and then manipulate these to fabricate a variety of structures suitable for several generic biomedical applications, tissue engineering, and biosensor coatings. Using BSA solutions with varying concentrations (20, 25, and 30 wt %) and cross-linking (terephthaloyl chloride) mechanisms, structures were fabricated including porous thin films with variable pore sizes and thickness (partially cross-linked coupled to bubble breakdown), scaffolds with variable pore morphologies (fully cross-linked), and coated bubbles (no cross-linking), which can be used as stand-alone delivery devices and contrast agents. The movement of typical biosensor chemicals (catechol and hydrogen peroxide) across appropriate film structures was studied. The potential of formed scaffold structures for tissue engineering applications was demonstrated using mouse cell lines (L929). In addition to low cost, providing uniform structure generation and high output, the size of the bubbles can easily be controlled by adjusting simplistic processing parameters. The combination of robust processing and chemical modification to uniform macromolecule bubbles can be utilized as a competing, yet novel, tool with current technologies and processes in advancing the biomaterials and biomedical engineering remits.